Geração automática de SDK em ES6 para APIs do Ginga CCWS - Abreu, Raphael; Santos, Joel A. Ferreira dos; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
The evolution of the Ginga standard for Digital TV requires tools that facilitate the adaptation and development of interactive applications. This article presents an SDK generator in JavaScript (ES6) based on the OpenAPI (Swagger) specification of the Ginga CCWS standard for TV 2.5 (ABNT NBR 15606-11). The SDK has the potential to simplify the interaction with the CCWS API services of the TV receiver, promoting interoperability and speeding up the development of applications for Brazilian Digital TV. In addition, the use of OpenAPI guarantees adaptability to future versions of the standard, facilitating the updating and maintenance of applications.